Effects of acupuncture on earthquake survivors with major psychiatric disorders and related symptoms: A scoping review of clinical studies. - Chan-Young Kwon; Jungtae Leem; Da-Woon Kim; Hui-Ju Kwon; Hyun-Seo Park; Sang-Ho Kim (PLoS ONE)
Background This scoping review aimed to determine the current research status of acupuncture for major psychiatric disorder (MPD) in earthquake survivors. Method We followed the scoping review process described previously. A literature search on 14 electronic databases was conducted from inception to November 29, 2022. Data from the included studies were collected and descriptively analyzed to address our research question. Extracted data were collated, synthesized, and summarized the according to the analytical framework of a scoping review. Result This scoping review included nine clinical studies: four randomized controlled trials (RCTs) and five before-after studies. The most frequent MPD type among the included acupuncture studies was posttraumatic stress disorder (PTSD; 6/9, 66.67%). The most frequent acupuncture type was scalp electro-acupuncture (4/9, 44.44%), followed by manual acupuncture and ear acupressure/ear acupuncture (3/9, 33.33%). Studies using scalp electro-acupuncture all used common acupoints, including GB20, GV20, GV24, and EX-HN1. In general, the treatment period lasted between 4 and 12 weeks. Validated assessment tools for PTSD severity and accompanying symptoms were used for patients with PTSD, while the corresponding evaluation tools were used for patients with other diagnoses or clinical symptoms. Acupuncture-related adverse events were generally mild and temporary, such as mild bleeding and hematoma, and syncope was a rare but potentially serious adverse event (1/48 patients and 1/864 sessions over a treatment period of 4 weeks). Conclusion Acupuncture studies for MPD after an earthquake mainly focused on PTSD. RCTs accounted for around half of the included studies. Scalp electro-acupuncture was the most common acupuncture type, and EX-HN1 and GV24 were the most important acupoints in the acupuncture procedures for MPD. The included studies mostly used validated symptom assessment tools, though some did not. Clinical studies in this field need to be further expanded regardless of the study type. Protocol registration https://osf.io/wfru7/.